Evolution of Radif (identical ending syllable) in Couplet Poem Based on Literary Types - Mahdi Dehrami (مطالعات زبانی و بلاغی)
Some researchers consider the couplet poem to be different in terms of musical aspects. One of these differences is the less usage of identical ending syllable in couplet poem. This article will examine the identical ending syllable in couplet poem. Factors such as literary types, different periods of Persian poetry, description or narration may affect the amount of using this element. For this reason, this element has been investigated in the mystical literary genre (Hadiqat al-Hagiqah, Rahiq al-taghigh, Makhzan al-Asrar) and lyric genre (Varaqe and Golshah, Weiss and Ramin, Leilly and Majnoun) and emphasizing the thousand verses of each of them. The research shows the use of identical ending syllable in couplet poem has increased, over time. In addition, there is no significant difference between narrative and non-narrative poems in the use of identical ending syllable, but the distribution of identical ending syllable is not the same in different parts of couplet poem. In different literary genres, use of the identical ending syllable is different. In the lyric poems, Poets used less than mystical poem.